Art Therapy: A Complementary Treatment for Mental Disorders - Hu, Jingxuan; Zhang, Jinhuan; Hu, Liyu; Yu, Haibo; Xu, Jinping (Frontiers in Psychology, 2021)
Art therapy, as a non-pharmacological medical complementary and alternative therapy, has been used as one of medical interventions with good clinical effects on mental disorders. However, systematically reviewed in detail in clinical situations is lacking. Here, we searched on PubMed for art therapy in an attempt to explore its theoretical basis, clinical applications, and future perspectives to summary its global pictures. Since drawings and paintings have been historically recognized as a useful part of therapeutic processes in art therapy, we focused on studies of art therapy which mainly includes painting and drawing as media. As a result, a total of 413 literature were identified. After carefully reading full articles, we found that art therapy has been gradually and successfully used for patients with mental disorders with positive outcomes, mainly reducing suffering from mental symptoms. These disorders mainly include depression disorders and anxiety, cognitive impairment and dementias, Alzheimer’s disease, schizophrenia, and autism. These findings suggest that art therapy can not only be served as an useful therapeutic method to assist patients to open up and share their feelings, views, and experiences, but also as an auxiliary treatment for diagnosing diseases to help medical specialists obtain complementary information different from conventional tests. We humbly believe that art therapy has great potential in clinical applications on mental disorders to be further explored.